Democracy and compliance in public goods games - Carlo Gallier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
I investigate if, how, and why the effect of a contribution rule in a public goods game depends on how it is implemented: endogenously chosen or externally imposed. The rule prescribes full contributions to the public good backed by a nondeterrent sanction for those who do not comply. My experimental design allows me to disentangle to what extent the effect of the contribution rule under democracy is driven by self-selection of treatments, information transmitted via the outcome of the referendum, and democracy per se. In case treatments are endogenously chosen via a democratic decision-making process, the contribution rule significantly increases contributions to the public good. However, democratic participation does not affect participants' contribution behavior directly, after controlling for self-selection of treatments and the information transmitted by voting.
urn:nbn:de:bsz:180-madoc-435755
Keywords: C91; D02; D72; K42; 330; laboratory experiment; public good; democracy; endogenous institutions; voting; contribution rule; compliance